Economic Liberalization and Savings Rates - Kashif Mansori (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper considers the possibility that economic liberalization, by which is meant a reduction in tariffs, quotas, capital controls, and other government distortions of international transactions, may reduce private savings rates. A two stage approach is used to analyze a panel data set covering OECD countries during the past two decades. The conclusion is that there is a significant and robust relationship between economic liberalization and lower rates of savings. One implication is that at least part of the decline in savings rates in some countries over the past two decades may be explained by the liberalization process.
Keywords: 330